Legal Protection and the Role of the State in Online Lending and Online Arisan - Tirtakusuma, Andreas Eno (Journal of Law, Politic and Humanities, 2026)
In the contemporary world, economic activities have increasingly transformed into electronic transactions. The use of electronic technology in money-lending activities and arisan has shifted practices that were previously conducted face to face into more practical online formats. Electronic technology has significantly accelerated and simplified these processes. Online lending and online arisan have emerged as two phenomena that are becoming increasingly prevalent, particularly as the intensive use of digital devices has led to a high level of dependency within society. Technological developments have facilitated rapid access to cash through online platforms, while online arisan arrangements have made the organization of arisan activities considerably easier. Both phenomena generate substantial social and economic impacts; however, they also give rise to various challenges related to security and regulation. Further research is therefore required to understand the legal relationships and the resolution of legal consequences arising from the implementation of online lending and online arisan, as, in practice, online lending has frequently resulted in debtors becoming financially distressed and unable to meet their repayment obligations, while many arisan participants have been trapped in fraudulent arisan schemes. The issues examined in this study concern how online lending (pinjol) and online arisan (arisol) operate as economic activities within society, how they are regulated, and how state protection is provided in practice in relation to these activities. These issues are examined through normative legal research employing a statutory approach and a case approach, grounded in theories of obligations and legal protection. Ultimately, this study concludes that there is a need to provide guarantees for debtors and arisan participants, which may take the form of a dedicated protection institution or a mandatory insurance mechanism.